Dietary and cardio-metabolic risk factors in patients with Obstructive Sleep Apnea: cross-sectional study - Stelmach-Mardas, Marta; Mardas, Marcin; Iqbal, Khalid; Kostrzewska, Magdalena; Piorunek, Tomasz (PeerJ, 2017)
Background Little is known about the role of dietary intake in obstructive sleep apnea (OSA), which could prove important in improving clinical outcomes for people with obesity and/or cardiovascular disease within these populations. Reduction in energy intake typically results in weight loss, markedly improving metabolic parameters and ameliorating OSA severity. The aim of this study was to evaluate the association of dietary and cardio-metabolic risk factors with OSA severity. Methods This was a cross-sectional study. A total of 75 volunteers at risk of OSA were recruited from 153 patients suffering from sleep disturbance at the Department of Pulmonology, Allergology and Respiratory Oncology at the Poznan University of Medical Sciences. Polysomnography was used for OSA diagnosis. Sleep quality was assessed by the Pittsburgh Sleep Quality Index. Blood pressure, parameters of glucose (fasting glucose, glucose tolerance test) and lipid metabolism (TC, LDL-C, HDL-C, TG) were assessed using routine enzymatic methods. Dietary intake was evaluated by 24-hr dietary recalls and Food Frequency Questionnaire. Ordinal logistic regression models were used for association of background characteristics and dietary intake with OSA severity. All analyses were adjusted for age, sex, BMI, smoking and alcohol intake. Results A higher percentage of smokers were observed in patients with mild OSA, while alcohol intake was the highest in severe OSA patients. Approximately 60% of the studied patients were self-reported poor sleepers. Results from ordinal logistic regression models showed that higher intakes of alcohol intake were associated with increased odds of severe OSA; whereas higher HDL-C levels were associated with lower odds (OR 0.01; 95% CI [0.0003–0.55]). Significantly higher odds of high OSA severity were observed in patients with disturbed sleep stages and obstructive sleep apnea. Moreover, the investigation of nutrient intake in relation to OSA severity showed that a higher intake of dietary fiber was associated with decreased OSA severity (OR 0.84; 95% CI [0.71–0.98]). Conclusions The severity of OSA is related to higher alcohol consumption and disturbed sleep. The significantly lower dietary fiber intake in patients with severe OSA is of particular importance for dietary consulting in clinical practice, which may positively influence cardiometabolic outcomes.
Keywords: Diet; Biomarkers; Sleep apnea; Obesity; Cardio-metabolic; Risk factor